Jelly Bean - Lord, Cynthia (New York : Scholastic Press, 2014)
No pets are allowed in the apartment where Suzannah and her family live, so she volunteers at a local pet shelter and plays with the dogs and cats there--but when a child whose family is moving brings in her pet guinea pig, Jelly Bean, Suzannah promises that she will find him the perfect home.
Keywords: Animal shelters -- Juvenile fiction; Volunteers -- Juvenile fiction; Guinea pigs -- Juvenile fiction; Pets -- Juvenile fiction; Responsibility -- Juvenile fiction